REGENERASI TUNAS DAN AKAR DARI KALUS DAUN KACANG TANAH (Arachis hypogaea L.) VARIETAS KELINCI DENGAN KOMBINASI 2,4-D DAN BAP - Ida Royani; Lalu Zulkifili; Prapti Sedijani (Bioscientist : Jurnal Ilmiah Biologi, 2015)
This is aimed todeterminethe effect of 2,4-D and BAP onshoot regeneration of peanut (Arachis hypogaea L.) Kelinci variety. This research was conducted in tissue culture laboratory of BBI-PPH Narmada. Competely randomized design (CDR) was applied on this rescarch which involved 2 factorial concentration of (0-4 mg/L) 2,4-D and (0-2 mg/L) BAP for both shoot regeneration on MS medium speed of the emerging shoots, number of shoots, theroots appear, and the amount ofroots. Statistical analysis showed that 2,4-D and BAP affect the speed of the emerging shoots, number of shoots, rootsand the number of days appear roots, and there is the effect of the combination of 2,4-D and BAP. Fastest emerging shoots obtained on MS medium with the addition of 2mg/LBAP with an average of 90.33days and the highest number of shoots contained on MS medium with the addition of 1mg/LBAP with an average of 4.33 shoots. While the earliest root formation was found on MS medium with the addition of 1mg/L2,4-D.